Double Diaspora and Transgenerational Memory in Nikesh Shukla’s The One Who Wrote Destiny - Alhaisony, Anas Galet M (Journal of Ecohumanism, 2024)
This article offers a focused exploration of Nikesh Shukla’s The One Who Wrote Destiny (2018), delving into the challenges and complexities of the ’double diaspora’ experienced by British South Asian characters in the UK. Situated at the intersection of literary analysis and sociocultural studies, the study addresses the novel’s thematic core, emphasizing the lasting impact of racism and cultural displacement across multiple generations. Utilizing Jan Assmann’s framework of ’communicative memory’ and ’cultural memory,’ alongside Maya Parmar’s exploration of double diaspora, the study investigates the evolution of memory representation, highlighting the transformation from lived, embodied memory to mediated, cultural forms. Central to this research is the examination of double diaspora, as outlined by Parmar, exploring the migration of the Gujarati community from South Asia to East Africa and later to Britain, and the identity struggles arising from these dual displacements. Through this in-depth analysis, the article explores the intricate interplay between memory, generational shifts, and the unique challenges faced by twice-migrant communities. It provides valuable insights into the evolving nature of immigrant experiences, cultural identity, and belonging in the United Kingdom since the turn of the millennium. This analysis contributes to a broader understanding of how transgenerational memory and double diaspora influence cultural adaptation and identity formation within diasporic communities, reflecting wider sociocultural trends in contemporary Britain.